Growth,anatomy and ecophysiology of pres. under drought andseasonal variation of rainfall - Cruz, Yasmini da Cunha (2021)
Plants in their natural environment experience periods of low rainfall, high temperatures and variations in the water status of the soil. Water deficit is an important stress factor in plants that directly affects growth through anatomical, morphophysiological and biochemical changes. In response to this factor, plants can develop adaptations that denote tolerance or sensitivity. Adaptive responses depend on the duration, frequency, intensity and period of plant development when subjected to water stress. The precipitation regime influences the flooding level in wetlands exposes macrophytes to seasonal variations in water availability. Typha domingensis have invasive potential and grows in a wide range of variation from 0 to 115 cm. Therefore, the specie survives in partially dry environments, with a reduction of about 50% of the soil water potential, and in environments with a flood of 1.5 m from the leaf. The high phenotypic plasticity of T. domingensis denotes the development of adaptive traits for colonization and survival in environment considered adverse for many species. In addition, the specie has a high capacity for clonal reproduction and dispersion, colonizing large areas where it can cause damage to biodiversity. In this study, availed the anatomical, physiological and nutritional traits that condition the growth of T. domingensis plants grown under controlled and natural drought conditions, due to the seasonal variation of rainfall.